Jenis-Jenis Pohon di Hutan Kota Trembesi, Peulanggahan, Kota Banda Aceh - Fitri Yuliana; Zuriana Siregar; Irvianty Irvianty; Cut Nanda Defira; Suwarno Suwarno (Universitas Syiah Kuala, 2024)
Trembesi Urban Forest is one of the green open spaces in the Banda Aceh City area which has various types of trees. This research aims to determine the types of trees found in the Trembesi Urban Forest. Data collection was carried out using the census method. The parameter observed in this research is the type of tree. The results of this research showed that there were 31 tree species from 17 families with a total of 493 individuals.